PENGARUH LEADER MEMBER EXCHANGE, DAN KELELAHAN EMOSIONAL TERHADAP TURNOVER INTENTION PADA KARYAWAN PERTOKOAN DALUNG PERMAI - Kurniawan, Agung Wachid; Putra, Made Surya (E-Jurnal Manajemen, 2019)
The purpose of this study was to determine the effect of leader member exchange, and emotional fatigue on turnover intention on employees. This research was conducted in the shop of Dalung Permai. The number of samples is 89 employees, using the method of saturated samples or census. Data collection is done through interviews and questionnaires. The analysis technique used is multiple linear regression. Based on the results of the analysis it was found that LMX partially had a significant effect on turnover intention, this indicates that the higher the LMX value the lower the turnover intention. Emotional fatigue partially has a significant effect on turnover intention, this shows the higher the employee's emotional fatigue the higher the turnover of his intention. This study shows a negative and significant effect of LMX on turnover intention, and a significant positive effect of emotional fatigue on turnover intention. Keywords : Leader member exchange, emotional fatigue, turnover intention.